Measuring social capital: further insights - Elena Carrillo Álvarez; Jordi Riera Romaní (Elsevier, 2017)
Social capital is defined as the resources available to individuals and groups through membership in social networks. However, multiple definitions, distinct dimensions and subtypes of social capital have been used to investigate and theorise about its relationship to health on different scales, creating a confusing picture. This heterogeneity makes it necessary to systematise social capital measures in order to build a stronger foundation in terms of how these associations between the different aspects of social capital and each specific health indicator develop. We aim to provide an overview of the measurement approaches used to measure social capital in its different dimensions and scales, as well as the mechanisms through which it is presumed to influence health. Understanding the mechanisms through which these relationships develop may help to refine the existing measures or to identify new, more appropriate ones.